Sistem Informasi Penilaian Prestasi Kerja Pegawai dengan Metode Pengembang Perangkat Lunak Model Waterfall - Niken Candraningrum; Ponco Sunarko; Kasliono Kasliono (Journal of Information System Research (JOSH), 2023)
Providing an assessment of employee work performance is a method for evaluating their competence with the aim of development to produce competitive employees. A Civil Servant (PNS) who achieves good (high) work performance should get a reward (compensation) that is comparable. It aims to motivate and reward civil servants for improving performance. However, some opportunities can turn into threats if they are not anticipated, such as negative responses from the public if the government is unable to improve the quality of its employees' performance. Inaccurate and ineffective assessments can cause the process of assessing the performance and quality of State Civil Apparatus (ASN) to be inaccurate and inappropriate. Therefore, an assessment system is needed that is relevant, practical, reliable and acceptable so that the assessment results are more accurate good and useful for employees and personnel administration at the Pontianak Fisheries Training and Extension Center (BP3). This system refers to the Waterfall model, where the progress of a process is considered to flow continuously like a waterfall. In the waterfall model, each step must be sequential and you cannot proceed to the next step but must complete the first step then proceed to the second step, and so on. With the system that has been built, the employee performance appraisal process can be well-documented and more transparent. The results of testing using the black box testing method showed that the system functionality could meet all the expected requirement specifications.